Assessment of myocardial function in Retrievers with dilated cardiomyopathy using 2D speckle tracking echocardiography: a pilot study - Hamabe, Lina; Shimada, Kazumi; Hirose, Miki; Hasegawa, Mizuki; Takeuchi, Aki; Yoshida, Tomohiko; Azakami, Daigo; Mandour, Ahmed S.; Tanaka, Ryou (Frontiers in Veterinary Science, 2024)
Early diagnosis of canine dilated cardiomyopathy (DCM) is complicated by the presence of a prolonged asymptomatic phase, for which a comprehensive evaluation of myocardial function is essential. This pilot study was conducted to evaluate the myocardial function in dogs with DCM using two-dimensional speckle tracking echocardiography (2D-STE). Nine client-owned Retrievers with DCM and twelve client-owned clinically normal Retrievers were comparatively evaluated using standard echocardiography and 2D-STE. Dogs with DCM were characterized by significant dilation of the left ventricle (LV), thinning of the LV wall, and myocardial hypokinesis when compared to clinically normal dogs. The global strain analysis showed a significant reduction of strain in both radial and circumferential directions, and the regional strain analysis revealed a greater degree of myocardial dysfunction at the LV free wall in the circumferential direction in dogs with DCM. The regional strain analysis also demonstrated a difference in the pattern of contraction between dogs with DCM and clinically normal dogs. The results of this study illustrate the ability of 2D-STE to evaluate both global and regional myocardial function in dogs with DCM and show differences between dogs with DCM and clinically normal dogs.